Analisis Transparansi Dan Akuntabilitas Pengelolaan Dana Zakat Yatim Mandiri Medan - Mentari Indrianti; Wilda Sri Munawaroh Harahap (Jurnal Mirai Management, 2023)
This research aims to analyze the management of zakat funds at the Medan Mandiri Orphan Zakat Institution and analyze the form of transparency and accountability of the Medan Mandiri Orphan Zakat Amil Zakat Institution's financial reports for 2017-2019. The research method used is a qualitative method with descriptive analysis using primary and secondary data taken from financial report data as well as interview methods. The results of the research conclude that the Amil Zakat Yatim Mandiri Medan Institution. has a structured and organized management system, involving various divisions and sections in the process of collecting, distributing and disbursing zakat funds, and to improve community welfare, namely through an economic empowerment program for productive zakat management. Transparency and Accountability of LAZ Yatim Mandiri Medan's 2017-2019 financial reports regarding financial reports such as financial position reports, doubtful profit reports and cash flow reports which are prepared periodically.. Kata Kunci: Zakat Accounting, Transparency, Accountability, Management Of Zakat Funds